The telecommunications customer service model based on big data and data fusion strategy research - Yongmei Gao; Chunhua Ju; Fuguang Bao (Dianxin kexue)
The rapid development of mobile network and internet technology, laid the foundation for the development of mobile e-commerce, and a new mobile consumption patterns appeared. The user characteristics model was designed by analyzing a large number of mobile users data sources and characteristics, and mobile user service model with the context analysis was built. Then, the telecommunication data processing framework on the basis of Hadoop framework was built. And also the analyzation of telecommunication data fusion and service mining application was made. It can be supportive for the new mobile consumption, consumption custom and personalized recommendation and marketing, etc.